ANALISIS RESOURCE LEVELING PADA TENAGA KERJA STUDI KASUS : PROYEK JLLB TAHAP2 - Alyaa Athooya Minarosi; I Nyoman Dita Pahang Putra; Anna Rumintang Nauli (Fakultas Teknik, Universitas Wiraraja, 2023)
The West Ring Outer Line Project experienced delays in its implementation. One of the factors in the delay is the inefficient allocation of resources. Thus, research analyzes the allocation of resources in the JLLB project to make it more efficient. Equitable distribution of resources is carried out by adjusting the use of labor according to the real conditions of the field. From the analysis, there are 3 conditions with the first condition, namely the planning condition which has a duration of 262 days with very significant fluctuations, namely the use of labor as many as 49 workers/day in the 3rd week of May and 1 handyman/day in the 4th week of May, with a peak use of 63 craftsmen out of 70 available craftsmen. The second condition is that the real field conditions are obtained with a duration of 262 days with a total of 33 builders/day, so that they have good distribution of labor resources. The third condition is the condition after leveling, with the number of builders available is 70 workers/day, shown at 38 weeks it does not exceed 33 craftsmen/day, this is done based on real field data, theresults are very different before leveling is carried out. With the work duration being 17 days slower, the project duration will be 279 days, starting from April 14, 2021 to January 17, 2022. From the three conditions, it is concluded that each data has a very significant disparity.